Vehicle noise comfort level indication: A psychoacoustic approach - Paulraj, Murugesa Pandiyan, Prof. Madya; Sazali, Yaacob, Prof. Dr.; Andrew, Allan Melvin (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher’s homepage at http://ieeexplore.ieee.org/